2017
DOI: 10.1111/inr.12376
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain among nurses in Slovenian hospitals: cross‐sectional study

Abstract: Slovenian healthcare system planning needs a national strategy to successfully promote LBP preventive and controlling strategies. Management can plan preventive and curative measures to reduce low back pain prevalence among nursing personnel. Management should also implement policies reflecting research findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 43 publications
8
53
3
2
Order By: Relevance
“…It is important to offer early intervention to treat anxiety among nurses to prevent musculoskeletal disorders. Numerous studies have identified relevant factors similar to the results of our study: female gender [ 41 , 48 ], absenteeism [ 9 ], and psychosocial factors [ 8 , 12 , 16 , 31 , 32 , 34 , 35 , 39 , 42 , 48 51 ]. In Vietnam, a previous study in Haiphong in Vietiep hospital (which have the largest number of nurses) also illustrated some factors as the gender, stress, and high age associated with MSDs [ 19 ], which was similar to our study outcomes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is important to offer early intervention to treat anxiety among nurses to prevent musculoskeletal disorders. Numerous studies have identified relevant factors similar to the results of our study: female gender [ 41 , 48 ], absenteeism [ 9 ], and psychosocial factors [ 8 , 12 , 16 , 31 , 32 , 34 , 35 , 39 , 42 , 48 51 ]. In Vietnam, a previous study in Haiphong in Vietiep hospital (which have the largest number of nurses) also illustrated some factors as the gender, stress, and high age associated with MSDs [ 19 ], which was similar to our study outcomes.…”
Section: Discussionsupporting
confidence: 83%
“…The results of some studies in Asia are comparable to this result; for example, in Pakistan in 2015, it was illustrated that around 49.7% of nurses faced MSDs in their lumbar, and 35.4% of them complained about MSDs in their shoulders [ 36 ]; another study in Iran and in Hong Kong saw the same picture with 40% and 42%, respectively, of nurses reporting MSDs in their lumbar [ 37 , 38 ]; and one study in Nigeria (in Africa) showed that the rate of MSDs in lower back was 44.1% [ 30 ]. Although most studies have shown that lower back was the most common site, this prevalence was still modest when compared to that from other studies in Asia: in Japan (lower back 71.3%) [ 32 ], in Iran (73.2% in 2010 and 65.3% in 2014) [ 16 , 39 ], in China (64.83%) [ 14 ], and in Saudi Arabia (65.7%) [ 15 ]; and this was similar to other studies in Europe: in Portugal (60.9% in 2015 and 63.1% in 2017) [ 9 , 40 ] and in Slovenia (85.9%) [ 41 ]. Neck was also one of the most common sites of MSDs.…”
Section: Discussionsupporting
confidence: 82%
“…Of the nursing professionals who experienced presenteeism, the majority were female professionals. This was also observed in a study conducted in Slovenia 27 . Regarding the professional category, the presenteeism score was lower among nursing technicians.…”
Section: Discussionsupporting
confidence: 79%
“…The association of stress, anxiety and/or burnout with health-related causes has been demonstrated in several studies (Coutu et al 2015;Miraglia & Johns 2016;Skela-Savic et al 2017;Yang et al 2015). To this end, validated tools have been implemented for each of the conditions.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, they have mainly been performed in the healthcare sector, which deals with human care and where employees must be physically and mentally prepared to perform their tasks (Campos et al 2013;Cooper 1998;Hansen & Andersen 2008;Johns 2010). The nursing sector has been extensively studied in relation to role overload, high pressure at work, relationships with supervisors and mental health conditions (Perry et al 2015;Schneider et al 2017;Skela-Savic et al 2017). Several studies have also demonstrated how productive decreases in nursing attendance while presenteeism occurs (Aysun & Bayram 2017;Noben et al 2015Noben et al , 2014Umann et al 2014).…”
Section: Introductionmentioning
confidence: 99%